Дослідження методів машинного навчання при розробці програмного забезпечення для формування портфелю інвестора - Ласіцин, О. В. (ХНУРЕ, 2023)
Today, there are numerous options for both passive and active financial enrichment. Investing money to earn passive income is one of many possibilities. Despite the wide range of financial investment prospects, it is important to carefully choose the investment objective. Therefore, there is currently, and probably always will be, interest in the research field of portfolio optimization for investors